'Am I Less British?' Racism, belonging, and the children of refugees and immigrants in North London - Şimşek, Doğuş (FRINGE, 2024)
'Am I Less British?' focuses on the children of refugees and immigrants in North London, whose parents migrated from Turkey. Providing a rich ethnography of the lives of the children, the book studies their sense of identity, belonging and their transnational experiences. It aims to understand how the children position themselves within a range of locations (London, North London and Turkey), where they face class hierarchy, racism and discrimination, and explores how they think about their sense of belonging within the contemporary political context in Britain and Turkey. De-identifying themselves from national identities and holding onto the oppressed identities appear as new forms of resistance in response to racism and exclusion. The experiences of the young people reflect the complexity of their lives in changing political and social circumstances across the borders of nation-states, and the importance of other categories of identity, including local identities. Overall, the book argues that the intersections of local, national and transnational approaches, the political context through which the lives of young people are framed, and their sophisticated engagement with ideas of race, class, ethnicity and gender, are crucial in understanding their identity formation. Praise for 'Am I Less British?' 'This is a nuanced and deeply researched study of the changing meaning of identity, citizenship and belonging in today's Britain. Drawing on her research in London among the children of Turkish migrants and Kurdish refugees, Şimşek makes an important intervention in the conversations on Britishness that are helping to shape our society.' John Solomos, University of Warwick "Am I Less British?" is a beautifully crafted ethnography of young Londoners whose parents are Kurdish and Turkish. Their voices sing out from its pages and question what it means to be British and the exclusions that block an equal access to belonging and full citizenship. A brilliant, stunning and urgent analysis of young multicultural lives.' Les Back, University of Glasgow 'This is a wonderful addition to our understanding of conviviality in a postcolonial city. Here we learn from new generations of Londoners as they contend with what it means to feel at home, in any place, at any time.' Vron Ware, author of Who Cares about Britishness? (2007)